Awareness Among Rural Youth about Agriculture Related Livelihood Options in Hills of Uttarakhand (Indian Journal of Extension Education, 2020)
Uttarakhand state is blessed with rare biodiversity which gives a great opportunity for diversified farming and horticulture. Regardless of the livelihood options available for hill youth the migration rate have also been high from the hill districts of the state. Low awareness about the agriculture related livelihood options may be one of the reasons behind youth out-migration. Hence, the study was carried out in Tehri Garhwal district of Uttarakhand, with descriptive research design. Two blocks were selected by random sampling and under each block two villages were selected by simple random sampling method. Respondents were taken by census method. The results of the study revealed that out of total eighty five livelihood options related to agriculture and allied sectors, the awareness among rural youth was found to be low on 43 options, medium in the 18 areas and high level of awareness in 24 areas as they were being traditionally cultivated in the area. The outcome of the study may be used by stakeholders to strengthen the information communication network for ultimately providing a sustainable livelihood to the rural youth and to reverse the out-migration from the hills of Uttarakhand.